Plant species as a therapeutic resource in areas of the savanna in the state of Pernambuco, Northeast Brazil. (2nd August 2015) - Saraiva, Manuele Eufrasio; Ulisses, Ana Vartan Ribeiro de Alencar; Ribeiro, Daiany Alves; Oliveira, Liana Geraldo Souza de; Macêdo, Delmácia Gonçalves de; Sousa, Francisca de Fátima Silva de; Menezes, Irwin Rose Alencar de; Sampaio, Everardo Valadares de Sá Barretto; Souza, Marta Maria de Almeida
Abstract: Ethnopharmacological relevance: Ethnobotanical studies have contributed significantly in research of plants with therapeutic potential. The aim of the present study was to learn about the use of native medicinal plants cited by the traditional population in "cerradão" (savanna woodland) areas in Northeast Brazil, providing data on therapeutic indications of the species used and their versatility. Materials and methods: Semi-structured interviews were conducted on the basis of a standardized questionnaire designed for key informants selected using the "snowball" technique. The selection of plants species with therapeutic potential was performed on the basis of the relative importance (RI) and informant consensus fator (ICF). Results: A total of 78 species were indicated for 87 therapeutic purposes. Of these, 11 species presented great versatility of use (RI>1), as e.g.including Copaifera langsdorffii Desf., Hybanthus calceolaria (Mart.) Plumel., Heliotropium cf. indicum L., Croton zehntneri, Croton heliotropiifolius, Myracrodruon urundeuva, Stryphnodendro rotundifolium . Medicinal uses could be generalized Pax & K. Hoffm and Hymenaea courbaril L. The therapeutic indications were grouped into 14 use15 categories with 594 species–category combinations. The largest number of medicinal species was indicated for illnesses or undefined pain, followed by diseases associated with respiratory, digestive and genitourinaryof body systems. The factor informant consensus highlighted the agreement in the use of plants and showed that the, of which Diseases of the Nervous System and, Diseases of the Circulatory System had the greatest agreement 1.0 and 0.87 repectively, Disorders of the Visual Sensory System – Eyes and Respiratory System Disorder showed the highest agreement of use. Conclusions: Most of the species cited by the key informants are well known scientifically, but it is interesting that some have been studied little or not all with regard to confirming their purported medicinal properties and can contribute substantially to pharmacological and phytochemical investigations in the search for new drugs. Graphical abstract: